A new species of karst-adapted gecko (Squamata, Gekkonidae, Gekko) from Guangxi, southern China - Zhong Huang; Hao-Tian Wang; Shuo Qi; Han-Ming Song; Yong Huang; Ying-Yong Wang; Yun-Ming Mo (ZooKeys)
A new species of the genus Gekko Laurenti, 1768, Gekko fengshanensis sp. nov., is described based on six specimens from Fengshan County, Hechi City, Guangxi Zhuang Autonomous Region, China. It is placed into the subgenus Japonigekko based on morphological and molecular phylogenetic analyses, and distinguished from consubgeners of Japonigekko by a combination of morphological characters in body size, cephalic proportions, and pholidosis features. Molecular phylogenetic analyses using mitochondrial 16S and ND2 sequences reveal that G. fengshanensis sp. nov. forms a sister relationship with G. kwangsiensis, collectively forming a clade with G. liboensis and G. paucituberculatus endemic to southern China’s karst ecosystems. This discovery increases the number of recognized Gekko species in the South China Karst to five, underscoring the role that fragmented karst landscapes play in driving speciation and maintaining high levels of biodiversity in this unique ecosystem.